2021
DOI: 10.3390/nu13041085
|View full text |Cite
|
Sign up to set email alerts
|

Heat Acclimatization, Cooling Strategies, and Hydration during an Ultra-Trail in Warm and Humid Conditions

Abstract: The aim of this study was to assess the history of exertional heat illness (EHI), heat preparation, cooling strategies, heat related symptoms, and hydration during an ultra-endurance running event in a warm and humid environment. This survey-based study was open to all people who participated in one of the three ultra-endurance races of the Grand Raid de la Réunion. Ambient temperature and relative humidity were 18.6 ± 5.7 °C (max = 29.7 °C) and 74 ± 17%, respectively. A total of 3317 runners (56% of the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Drinking plenty of liquids during races is recommended to avoid dehydration [ 1 ]. Different hydration strategies are used during ultratrail races to avoid dehydration [ 85 ]. The problems of dehydration regarding metabolic and neuromuscular performance were previously outlined [ 25 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drinking plenty of liquids during races is recommended to avoid dehydration [ 1 ]. Different hydration strategies are used during ultratrail races to avoid dehydration [ 85 ]. The problems of dehydration regarding metabolic and neuromuscular performance were previously outlined [ 25 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in the overall rate of exercise-related injuries across a 12-month period; however, female athletes suffered a disproportionate number of stress fractures [ 52 ]. Females were more likely to encounter medical illness during a race, with one study demonstrating four times the risk of developing an AKI during a multi-stage ultramarathon compared to males [ 53 , 54 ]. One study found that males were significantly more likely to report a history of heat-related illness and muscle cramps, and to experience heat-related symptoms during an ultramarathon [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Stress fractures were more common among females, compared with males ( p < 0.001) Khodaee et al (Abstract only) [ 57 ] 308 athletes who completed a 100 mile ultramarathon. Sex split not reported Race-related injuries requiring medical attention post-race Cross-sectional Low No sex differences in incidence of race-related injuries requiring medical attention Krabak et al[ 53 ] 396 athletes (20.8% females, 79.2% males) who completed a 250 km 7-day trail ultramarathon Rate of medical illness and injury Cohort study Low Females were 16% more likely to encounter medical illness when adjusted for age and race hours No difference in overall injury/illness rates, skin problems, or MSK injuries Lipman et al[ 54 ] 128 athletes (28% females and 72% males) who competed in a 250 km multi-stage ultramarathon Changes in serum creatinine, cumulative incidence and prevalence of AKI Cohort study Low Overall cumulative incidence of AKI was 41.4%. Odds ratio for females and AKI was 4.64 (95% CI 2.07–10.37, p < 0.001) Hoffman et al[ 58 ] 201 athletes who completed a 161 km ultramarathon.…”
Section: Resultsmentioning
confidence: 99%
“…Another limitation is that we had no data about the training and pre-race experience of these participants [ 53 ], such as details of nutrition and fluid intake would have been of interest [ 55 ] that are associated with energy distribution across the race. Furthermore, the influence of course elevation and environmental conditions such as weather was not considered [ 56 ]. Unfortunately, we could not consider physiological and pathophysiological aspects in this analysis [ 57 ].…”
Section: Discussionmentioning
confidence: 99%